Effects of U74389G on pulmonary macrophage influx and lung development in 95% O2 exposed newborn rats - Luo, Xiao-ping (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2004)
OBJECTIVE: Oxygen toxicity is believed to play a critical role in the pathogenesis of bronchopulmonary dysplasia (BPD). U74389G, a potent 21-aminosteroid antioxidant, was applied to the 95% O(2) induced acute lung injury in newborn rat model. The present study aimed to investigate the mechanism of hyperoxic lung injury and the interaction of possible mediators, and to explore the effect of antioxidant intervention